Mechanical Study of Stabilised Earth Bricks with Eucalyptus Ash - Kuma, Mbuh Moses; Alakeh, Mofor Nelson; Valentin, Makomra; Ndiyun, Fangfoh Louis; Randy, Aponleneh (European Journal of Applied Sciences, 2025)
Background: Given the growing concern and awareness regarding sustainable building material and environmental issue, Stabilized Earth Brick (SEB) gives the view of energy efficiency and the cost reduction of materials. And due to the limited supply of sand for cement blocks/bricks and the price of cement to be used for construction as well as the weak bricks and expensive nature of importing fire bricks in our locality. Materials: This research was aimed at stabilizing earth from a pit at BANGSHIE with eucalyptus ash to be used for construction which was achieve by sitting apart the soil at a depth of (50-100) cm from the earth surface and some Geotechnical studies carried out. Results: The studies shows that the laterite was a clay material composed of 0.6% gravel, and 14.7% sand, and the optimal dry density of 1.608 and water content 21.2% from the proctor test. The Atterberg limits test has also reveal that the soil had liquid limit of 60.0, plastic limit of 50.0 and the Plasticity index of 10.0 from which our soil was classify as A-5 using the universal soil classification system. Fifty-six (56) samples with 0 %. 5%, 10 %, 15 %, and 20 % of eucalyptus ash were moulded and the compressive strength, and total water absorption test carried out which revealed that the more the percentage of eucalyptus wood ash (EWA) the more the strengths and water absorption. With the maximum compressive strength of 1.56 MPa, and water absorption of 10.04% after 28 days. Conclusion: From these results, it was seen that for works in non-humid environment the percentage of EWA should be 20% and are economical as per using other construction materials such as the sand, cement and sundry brick.